Investigation on Indigenous Bacillus Isolates With Bioremediation Properties for Improving Water Quality and Shrimp Health in Malaysian Aquaculture - Devaraja, T. N. (2002)
Indigenous marine bacteria of the genus Bacillus were selected to study their properties as potential use for bioremediation owing to their inherent versatility. Bacteria were isolated from water and sediment samples collected along the west coast of Peninsular Malaysia in brackishwater environment. Selected isolates were identified to species level using biochemical and API CH kit and three suitable isolates, Bacillus pumilus AB58, B. subtilis AB65 and B. lichenifonnis AB69 were selected for the study. Optimum growth requirements of temperature, NaCI and pH were 30°C, 1.5% and 7.5 respectively, determined for the isolates by measuring the optical density and corresponding cell number. The growth curves of the isolates were plotted and all of them reached maximum cell number during a 16-20 h incubation. The cell density in overnight cultures of B. pumilus AB58, B. subtilis AB65 and B. licheniformis AB69 were 5.7xl09 (± 0.8), 3.7xl08 (± 0.6), 5.0x109 (± 0.6) cfu/ml respectively. They had the ability to tolerate ammonia levels of up to 20 mg/l without a considerable change in cell numbers for 48 h. However, the growth was suppressed completely at 25 mg/l of ammonia. At 40 ppt salinity, all the isolates survived for 4 days without significant change in initial cell numbers (108 cfu/ml). The selected isolates were found to secrete extracellular enzymes viz., protease, gelatinase, amylase and lipase as detected by clear zone formation on substrate based agar plates. Bacillus pumilus AB58 and B. subtilis AB65 produced significantly (P < 0.05) bigger protease clear zones (19.0 ± 2.0 and 23.0 ± 4.0 diameter in mm respectively) than B. licheniformis AB69. However, B. subtiUs AB65 secreted significantly (P < 0.05) more amylase (31.0 ± 5.0 diameter in mm) than the other two isolates. All the isolates were sensitive to most of the antibiotics tested on MHA plates. These isolates were compatible with each other in mixed culture conditions. They inhibited as well as excluded all the pathogenic vibrios (Vibrio algillolyticus MIl, V. alginolyticus M12, V. parahaemolyticus MI, V. parahaemolyticus M3, V. parahaemolyticus M6, V. alginolyticus T, V. parahaemolyticus T, V. harveyi I and V. parahaemolyticus I) tested by diffusion disc, streak plate and common broth methods. Synergistic effect of isolates had significantly higher (P < 0.05) inhibition of all vibrios than the individual isolates. The isolates were confirmed for their non-pathogenicity to shrimp postlarvae (PL 29). All three isolates were tested for their effect on ammonia in simulated pond conditions. All non-aerated treatment tanks had significantly lower ammonia levels (P < 0.05) than the non-aerated control tanks, which were not treated with bacterial isolates both in case of single and combination treatments. Synergistic effect of isolates reduced the ammonia levels at a faster rate than the treatments with single isolate. Sediment properties were not significantly different between treated and control groups except for the total and available phosphorous levels, which were significantly higher in tanks treated with B. licheniformis AB69 (P < 0.05) compared to the others. The selected Bacillus isolates satisfied the criteria to qualifY them for bioremediation in aquaculture.